Impact of intravenous heparin on quantification of circulating microRNAs in patients with coronary artery disease - Kaudewitz, Dorothee; Lee, Regent; Willeit, Peter; McGregor, Reuben; Markus, Hugh S.; Kiechl, Stefan; Zampetaki, Anna; Storey, Robert F.; Channon, Keith M.; Mayr, Manuel (Thrombosis and Haemostasis, 2013)
MicroRNAs are small non-coding RNAs that are detectable in plasma and serum. Circulating levels of microRNAs have been measured in various studies related to cardiovascular disease. Heparin is a potential confounder of microRNA measurements due to its known interference with polymerase chain reactions. In this study, platelet-poor plasma was obtained from patients undergoing cardiac catheterisation for diagnostic coronary angiography, or for percutaneous coronary intervention, both before and after heparin administration. Heparin had pronounced effects on the assessment of the exogenous C. elegans spike-in control (decrease by approx. 3 cycles), which disappeared 6 hours after the heparin bolus. Measurements of endogenous microRNAs were less sensitive to heparin medication. Normalisation of individual microRNAs with the average cycle threshold value of all microRNAs provided a suitable alternative to normalisation with exogenous C. elegans spike-in control in this setting. Thus, both the timing of blood sampling relative to heparin dosing and the normalisation procedure are critical for reliable microRNA measurements in patients receiving intravenous heparin. This has to be taken into account when designing studies to investigate the relation of circulating microRNAs to acute cardiovascular events or coronary intervention.
Keywords: Cardiology; coronary syndrome; clinical trials; heparins